Impact of Biomass Recycling and Fertilization on Soil Microbiological Characteristics and Wheat Productivity in Semi-Arid Environment - Govind Kumar Yadav; Sunil Kumar Dadhich; Rajendra Kumar Yadav; Rajesh Kumar; Jalpa Dobaria; Bilal Ahamad Paray; Soon Woong Chang; Balasubramani Ravindran (Agronomy, 2023)
In India, 700 million tons of agricultural waste generated annually is burned by farmers in the fields, which decreases biological activity in soil. The issue of handling the enormous amounts of crop residues that emerge from increased crop output might be resolved by composting. However, different crop residues improve soil physico-chemical and biological properties in different ways. Crop residue incorporation and fertilization (NPK) impact crop productivity due to changes in soil microbial biomass carbon, nitrogen, phosphorous, and the soil enzymatic activity. A field experiment was conducted for two years (2020–2021 and 2021–2022), which comprises five partially composted crop residues treatments viz., control, clusterbean straw, groundnut shell, pearlmillet husk, and sesame stover (added at rate of 5 t ha−1), and four fertilization (NPK) treatments viz., control, 75% RDF, 100% RDF, and 125% RDF. The microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), microbial biomass phosphorus (MBP), enzymatic activities in soil and wheat yield were studied under a semi-arid environment (India). Data showed that the continuous application of crop residues and fertilizer significantly affected MBC, MBN, MBP, and soil enzymatic activity after two years of experimentation in a semi-arid region environment. The highest levels of microbial biomass (viz, MBC, MBN, MBP) and enzyme activities were noticed in the sesame stover and 125% recommended dose of fertilizer (RDF) treatments. Therefore, this study highlights the need for restoring crop residue for effective soil management. The crop residue and NPK fertilization are more efficient in improving the soil’s microbial properties and the yield of wheat.